The people of Denendeh : ethnohistory of the Indians of Canada's Northwest Territories - Helm, June, 1924- (University of Iowa Press, 2000)
For fifty years anthropologist June Helm studied the culture and ethnohistory of the Dene, "The People," the Athapaskan-speaking Indians of the Mackenzie River drainage of Canada's western subarctic. Now in this impressive collection she brings together previously published essays - with updated commentaries where necessary - unpublished field notes, archival documents, supplementary essays and notes from collaborators, and narratives by the Dene themselves as an offering to those studying North American Indians, hunter-gatherers, and subarctic ethnohistory and as